Pengaruh Komitmen Organisasi Dan Penerapan Prinsip-Prinsip Good Governance Terhadap Kualitas Pelayanan Di Baperlitbang Kabupaten Banjarnegara - Lustono Lustono; Laela Fitriyanti; Ratna Suryani (Medikonis, 2021)
ABSTRACT The problem in this study is the effect of organizational commitment and the application of good governance principles on service quality. This research is located at the Research and Development Planning Agency of Banjarnegara Regency, this study aims to explain the influence of organizational commitment variables and the application of good governance principles in a passive and simultaneous way on service quality. This research is a quantitative research. The data used in this study is primary data with a questionnaire technique. The population in this study are people who carry out research permits and data request permits in the Research, Development and Planning Program. The sampling technique in this study is to use the slovin calculation and obtained a sample of 100 respondents. Data analysis in this study used multiple linear regression analysis with SPSS 24 software. The results of this study indicate that partially the organizational commitment variable has no effect on service quality and the variable application of the principles of good governance has a positive and significant effect on service quality. Meanwhile, simultaneously organizational commitment and the application of good governance principles affect service quality.